Inhibitory effect of clove methanolic extract and eugenol on dendritic cell functions. (December 2016) - Lin, Ching-Hsiung; Lin, Sheng Hao; Lin, Chi-Chen; Liu, Yi-Chen; Chen, Chao-Jung; Chu, Ching-Liang; Huang, Hui-Chi; Lin, Ming-Kuem
Highlights: This is the first report on the effect of clove on dendritic cell (DC) functions. Clove methanolic extract and eugenol inhibited DC functions. The extract and eugenol halted the T-cell proliferation through DC function. Clove and eugenol inhibited delayed-type hypersensitivity response. Graphical Abstract: Abstract: Caryophyllata Flos or clove is widely used as a condiment and in Chinese medicine. It reportedly helps relieve asthma and allergies; however, the underlying mechanisms remain unclear. In particular, the mechanism affecting dendritic cells (DCs), which play a critical role in the immune response, remains unknown. In this study, we examine the effects of Caryophyllata Flos methanolic extract (CFME) and its major compound, eugenol, on DC functions. Our results showed that CFME and eugenol significantly inhibited DC activation and maturation. The IC50s of CFME and eugenol were approximately 25 µg/mL and 50 µM, respectively. CFME and eugenol halted T-cell proliferation. Contact hypersensitivity responses were inhibited in mice cosensitized with either CFME or eugenol. We demonstrated for the first time that clove and its major active ingredient, eugenol, exhibited a significant immunosuppressive effect on DC functions, revealing that clove is a functional food that can ameliorate chronic inflammation and autoimmunity.